Prevalence of odontogenic sinus tracts in patients referred for endodontic therapy - Ali Mert; Elif Soğur; Güniz Baksı; Hakan Sen (Cumhuriyet University, 2013)
Objectives: The primary aim of this study was to assess the prevalence, location and distribution of odontogenic sinus tracts in a population of Turkish adult patients referred for endodontic therapy. The second aim was to investigate the influence of the factors such as sex, age, systemic disease, existence and diameter of periapical radioluceny on the prevalence of the clinically detected sinus tracts among Turkish population. Materials and Methods: A total of 499 patients' records according to the demographic data and the presence of periapical radiolucency and of sinus tract were included to the present study. The location of the sinus tracts was recorded as well. Data were analyzed using Pearson chi-square and Fisher's Exact Tests (p=0.05). Results: The number of the teeth who had sinus tracts was 37 (7.4%). Sixteen of 37 teeth with sinus tracts were associated with posterior teeth (43%). No significant differences were found in the prevalence of sinus tracts between two genders (p>0.05). 40-50 year age group showed the highest prevalence of sinus tracts. Conclusions: Approximately one in thirteen teeth referred for root canal treatment had a sinus tract. Fourty-three percent of sinus tracts were associated with posterior teeth with high prevalence of openings in buccal aspects of the gingiva. Therefore, practitioners should be careful while examining posterior teeth referred for endodontic treatment.